Complications during surgical treatment of incarcerated inguinal hernia - Krivokuća Božo; Jakovljević Aleksandar; Savić Ostoja; Krivokuća Svetozar; Stanković Stefan (Scripta Medica, 2017)
Introduction: An incarceration of inguinal hernia is a life-threatening condition and represents the most frequent complication, particularly in the elderly patients. It may compromise vascularisation of the contents of the hernia. A surgical treatment of the incarcerated inguinal hernia represents one of the most frequent surgical interventions in elderly patients and it grows proportionally with the age. Aim of the Study: The aim of the study is to investigate some of the factors that may have an impact on the incarcerated inguinal hernias surgical treatment outcome in elderly patients. Patients and Methods: The study included 149 patients classified in two groups: the study group (> 60 years of age), which included 96 patients, and the control group (≤ 60 years of age), which included 53 patients, treated in the period from January 1st, 2012 to December 31st, 2016 at the Clinic of General and Abdominal Surgery UCC RS Banja Luka. Results: Most of the patients had right inguinal hernia (51.16% in the study group, 60.37% in the control group). 82 patients (85.41%) of the study group suffered from some of the accompanying chronic diseases, opposite to 20 patients (37.73%) of the control group. Polypropylene mesh was implanted in 105 (70.47%) patients, while the tension technique was performed in 44 (29.53%) patients. The duration of incarceration longer than 24 h (p=0.015), previous abdominal surgery (p=0.001), the American Society of Anaesthesiologists physical status classification system (ASA classification) (p=0.033) and the presence of chronic diseases (p=0.01) appeared to be statistically significant risk factors for performing intestinal resection in the study group, while in the control group, they represented risk factors, but not at the level of statistical significance (p > 0.05), except for the duration of incarceration (p=0.007). A higher ASA stage (p=0.001), is the most important risk factor for lethal outcome in both groups of patients. Conclusion: Incarcerated inguinal hernia is a very serious and demanding surgical problem, particularly in elderly patients. A higher ASA score and the presence of bowel resection are the most important risk factors related to very difficult complications.